Tuvan paremiology: its linguoculturological and linguoaxiological potential - Lomakina, Olga V. (The New Research of Tuva, 2022)
The article examines the paremiology of Tuvan language in its linguoculturological and linguoaxiological aspects, with a focus on Tuvan paremies as a source of cumulative information which reflects the system of value-based reference points, and transmits customs and traditions through images and notions. The sources for our study were the Tuvan paremies found as a continuous sample in Ya. Sh. Khertek’s “Tuvan-Russian phraseological dictionary”, E. R. Tenishev’s “Tuvan-Russian dictionary”, M. Khadakhane and O. Sagan-ool’s “Tuvan proverbs and sayings”, and B.K. Budup’s “Proverbs and sayings of the Tuvan people”. The author, relying on the theoretical findings of contemporary paremiology, proves that the term “paremiological system” can be used to describe the entirety of the language’s paremiological resources. The word “paremia” can be used as an umbrella term to refer to all of the smaller genres of the folklore, with the proverb as the most frequent among them. The article provides some examples of how to describe the linguoculturological and linguoaxiological capabilities of the proverbial corpus of the Tuvan language. The author has shown that the linguoculturological aspect of the Tuvan paremies is linked to their prototypical situation and depends on the ethnocultural meaning of their components which act as ethnolinguomarkers. Meanwhile, paremies’ linguoaxiological content is a balance between the universal and ethnoculturally unique values possessed by the Tuvan people. The article provides examples of both the value constants and the value variables as represented in Tuvan paremiology. Also outlined are the prospects of further studies in the paremiology of the Tuvan language.